2018
DOI: 10.1038/s41467-018-03127-w
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale kinetic segregation of TCR and CD45 in engaged microvilli facilitates early T cell activation

Abstract: T cells have a central function in mounting immune responses. However, mechanisms of their early activation by cognate antigens remain incompletely understood. Here we use live-cell multi-colour single-molecule localization microscopy to study the dynamic separation between TCRs and CD45 glycoprotein phosphatases in early cell contacts under TCR-activating and non-activating conditions. Using atomic force microscopy, we identify these cell contacts with engaged microvilli and characterize their morphology, rig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
85
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(90 citation statements)
references
References 41 publications
3
85
1
1
Order By: Relevance
“…Instead of waiting for passive close contact formation and hence TCR/pMHC binding, T cells actively produce close contacts. They use structures known as microvilli or invadosome‐like protrusions (ILPs) . These actin‐rich 100‐200 nm diameter protrusions enable T cells to push on nearby cells in order to achieve close membrane apposition compatible with TCR/pMHC interactions, which leads to CD45 segregation (Figure B).…”
Section: Mechanisms Of T‐cell Sensitivity To Antigenmentioning
confidence: 99%
See 2 more Smart Citations
“…Instead of waiting for passive close contact formation and hence TCR/pMHC binding, T cells actively produce close contacts. They use structures known as microvilli or invadosome‐like protrusions (ILPs) . These actin‐rich 100‐200 nm diameter protrusions enable T cells to push on nearby cells in order to achieve close membrane apposition compatible with TCR/pMHC interactions, which leads to CD45 segregation (Figure B).…”
Section: Mechanisms Of T‐cell Sensitivity To Antigenmentioning
confidence: 99%
“…They use structures known as microvilli or invadosome‐like protrusions (ILPs) . These actin‐rich 100‐200 nm diameter protrusions enable T cells to push on nearby cells in order to achieve close membrane apposition compatible with TCR/pMHC interactions, which leads to CD45 segregation (Figure B). It is noteworthy that these structures have short (approximately 5‐50 seconds) lifetimes without antigen, but upon antigen recognition, they can be stabilized for long (approximately 10 minutes) timescales .…”
Section: Mechanisms Of T‐cell Sensitivity To Antigenmentioning
confidence: 99%
See 1 more Smart Citation
“…However, how these molecules participate in translating the very initial TCR ligand occupancy events to productive TCR signaling is still poorly understood. Furthermore, while the involvement of multiple cytoskeletal elements in the formation of the IS has been documented (9)(10)(11)(12)(13), the role of cytoskeletal components in the initial antigen recognition events triggering TCR signaling remains unclear. While several T-cell related or more general models were proposed to explain protein distribution on cellular surfaces, (14-18) much remains to be learned about the organization of key surface receptors implicated in T-cell activation and the formation of functional immune synapses.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Krummel and coworkers demonstrated that microvilli function as sensors that scan the surface of encountered APCs within seconds (27). Sherman and co-workers also observed that microvilli are involved in early T-cell activation (12), and Jun and coworkers demonstrated that upon TCR activation T cells release nanoscale microvilli-related vesicles that interact with APCs and transfer cargo to these cells through a process termed trogocytosis (28).…”
Section: Introductionmentioning
confidence: 99%